2020
DOI: 10.1177/2633366x19897923
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone/calcium sulfate whisker/barium titanate piezoelectric ternary composites for tissue reconstruction

Abstract: The piezoelectric materials with excellent bioactivity have attracted more attentions recently and have broad potential applications in tissue engineering. In this article, the barium titanate (BT) particles were filled into the polycaprolactone (PCL)/calcium sulfate whisker (CSW) (15 wt%) composites to prepare the PCL/CSW/BT ternary composites. Due to the reinforcement synergy between the CSWs and the BT particles, the mechanical properties of the ternary composites were increased by 50% compared with the PCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Research by Liu et al [ 61 ] has shown that piezoelectric composites have great compatibility with bone cells that successfully increase cell viability by culturing cells on the composite matrix. The findings have displayed the potential application of piezoelectric materials that are appropriate for other types of body tissue engineering as well.…”
Section: Protein-based Smart Materials In Tissue Engineeringmentioning
confidence: 99%
“…Research by Liu et al [ 61 ] has shown that piezoelectric composites have great compatibility with bone cells that successfully increase cell viability by culturing cells on the composite matrix. The findings have displayed the potential application of piezoelectric materials that are appropriate for other types of body tissue engineering as well.…”
Section: Protein-based Smart Materials In Tissue Engineeringmentioning
confidence: 99%
“…Therefore, different materials (such as ceramic materials) are considered to progress PCL osteoconductivity and bioactivity. 22,23 Biodegradable polymers and bioactive ceramics combine to form a novel composite material with potential uses in tissue engineering, such as short-term bone implants, dental fillers, and biocompatible scaffolds. Polymers’ advantages, such as flexibility and deformability under stress, are preserved while the composite material’s strength and bioactivity are improved.…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL) is an organic component because of its adaptability and biodegradability has been considered much in tissue engineering applications [25].…”
Section: Introductionmentioning
confidence: 99%